Multiple sexually transmitted co-infections are associated with adverse reproductive outcomes in asymptomatic adolescent pregnant women; A Prospective cohort study - Wasnik, Kirti; Mittal, Pratima; Ghope, Priti; Sonkar, Subash C.; Arora, Geetika; Saluja, Daman (Frontiers in Medicine, 2022)
A prospective cohort was conducted to assess the prevalence of seven RTIs/STIs in adolescent asymptomatic pregnant women to find a significant correlation between infection and pregnancy. The study was restricted to 18-19 years of asymptomatic adolescent pregnant women attending Ante-Natal Care and the health status of the pregnant women was followed up to parturition. The health status of the infant was followed till six months post-delivery. The prevalence of the concerning pathogens and the significance of their association with adverse outcomes of pregnancy were determined. Among 279 subjects, the most significant co-infections were observed for M. hominis with U. parvum (9•31%; p-value-0•0071/OR-2•6421) and U. urealyticum (7•88%; p-value-0•0119/OR-2•6455). Statistically significant associations were found between C. trachomatis ([p-value-0•0439]; OR-2•9902) and M. genitalium ([p-value-0•0284]; OR-3•442) with PTB, N. gonorrhoeae with LBW <2.5Kg([p-value-0•0052];OR-4•9017)), U. urealyticum with VLBW <2kg([p-value-0•0262];OR-3•0207), M. genitalium (p-value-0•0184]; OR-11•7976) and T. vaginalis with PROM ([p-value 0•0063]; OR-19•4275) while M. genitalium ([p-value 0•0190] ; OR-12•9230) and U. urealyticum ([p-value 0•0063]; OR-14•5149) with PPROM with 95% CI respectively. Asymptomatic adolescents are at high risk of adverse pregnancy outcomes if infected with the concerned pathogens.